The state of the vegetative regulation of drivers of the passenger electric depending on the experience of professional activity - Gorsha, V. I.; Gozhenko, A. I.; Gorsha, O. V. (Journal of Education, Health and Sport, 2016)
Gorsha V. I., Gozhenko A. I., Gorsha O. V. The state of the vegetative regulation of drivers of the passenger electric depending on the experience of professional activity. Journal of Education, Health and Sport. 2016;6(10):821-831. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.268645 http://ojs.ukw.edu.pl/index.php/johs/article/view/4235 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. UDК 616 — 092.11: 656.02 – 092 The state of the vegetative regulation of drivers of the passenger electric depending on the experience of professional activity V. I. Gorsha, A. I. Gozhenko, O. V. Gorsha Ukrainian Scientific Research Institute of Medicine of Transport of the Ministry of Health of Ukraine, Odessa, gorshao@mail.ru Abstract The aim of the research was to study the state of autonomic regulation of persons with a high level of professional and emotional load that is to say about drivers of the passenger electric transport depending on the experience of professional activity. The state of vegetative regulation was defined according to the heart rate variability (method of cardiointervalography), activity and biorhythmic of stress hormones – cortisol and catecholamines. The state of vegetative regulation of the mechanisms of adaptation for the drivers of passenger electric transport begins to change after 5 years of work as activation of the parasympathetic section of vegetative regulation and independent contour of control. The hormonal link of the regulation of the mechanisms of adaptation for the drivers of the passenger electric transport also depended on the experience of their work, which appeared of the different activity and biological rhythm of the stress hormones -cortisol and catecholamines. Key words: drivers of passenger transport, professional adaptation, vegetative regulation, heart rate variability, stress hormones.